Performing the Gospel: orality, memory, and Mark; essays dedicated to Werner Kelber - Horsley, Richard A.; Kelber, Werner H.; Draper, Jonathan A.; Foley, John M. (Fortress Press, 2006)
This ground-breaking volume gathers the best new work in Gospel's criticism centered on how the Gospels actually came to be: through oral tradition, story performance, and cultural memory. The contributors include: John Miles Foley, Martin Jaffee, Jonathan A. Draper, Ellen Aitken, Holly Hearon, Vernon K. Robbins, Whitney Shiner, Jan Assmann, Jens Schroeter, and Richard A. Horsley.